2020
DOI: 10.1177/0022002720939304
|View full text |Cite
|
Sign up to set email alerts
|

Street-level Repression: Protest, Policing, and Dissent in Uganda

Abstract: In many countries, police are both guardians of public safety and the primary instruments of state repression. Used to quell dissent, excessive police action can drive further collective action, leading to a repression-dissent nexus. Yet does repression spur dissent for all, or only for those already dissenting? We theorize repression by police causes political backlash, decreasing support for police and increasing political dissent. We argue these effects are conditioned by individuals’ proximity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 86 publications
2
37
0
Order By: Relevance
“…Our main contribution is to provide evidence of the impact of police repression on protest decisions using individual-level administrative data. Previous research has studied the impact of police and state repression on dissident behavior using laboratory evidence, online surveys, and aggregate data (García-Ponce and Pasquale, 2015;Lawrence, 2017;Aytac et al, 2018;Young, 2019b;Rozenas and Zhukov, 2019;Curtice and Behlendorf, 2020;Bautista et al, 2020a). 3 There are two novelties in our analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Our main contribution is to provide evidence of the impact of police repression on protest decisions using individual-level administrative data. Previous research has studied the impact of police and state repression on dissident behavior using laboratory evidence, online surveys, and aggregate data (García-Ponce and Pasquale, 2015;Lawrence, 2017;Aytac et al, 2018;Young, 2019b;Rozenas and Zhukov, 2019;Curtice and Behlendorf, 2020;Bautista et al, 2020a). 3 There are two novelties in our analysis.…”
Section: Introductionmentioning
confidence: 99%
“…While the NRM undoubtedly enjoys pockets of popular support, to retain power it resorts to manipulation of state resources, intimidation by security forces, and politicized prosecutions of opposition leaders. The UPF thus serves a dual purpose (Curtice and Berhlendorf 2020): on the one hand, like any police force, it is responsible for protecting the life and property of Ugandan citizens, and for maintaining security and enforcing the laws (The Police Act 1994, Article 4). On the other hand, it has also been tasked with quelling dissent and intimidating the political opposition-especially during election periods-in the service of Museveni and the NRM (Kagoro 2015).…”
Section: Police-community Relations and Cop In Ugandamentioning
confidence: 99%
“…Uganda Police Force (UPF) lacks independence from political influence, and the ruling party routinely misuses the UPF's coercive capability to advance its partisan goals, especially in the months preceding national elections (Curtice and Berhlendorf 2020).…”
mentioning
confidence: 99%
“…Generally, these mechanisms coincide with notions of fairness, voice, and neutrality or impartiality, which comprise key elements of procedural justice policing (Mazerolle et al, 2013;Trinkner & Tyler, 2016;Tyler & Blader, 2003). The use of excessive force or repressive tactics against protestors violates these principles and can damage the trustworthiness of police (Curtice & Behlendorf, 2021;Nägel & Lutter, 2021;Perry et al, 2017). Research that has used disaggregated measures of perceptions of police and legitimacy has found that the use of excessive force and violence during protests is associated with declines in perceptions of police fairness, feelings of obligation to obey, and normative alignment with police (Curtice, 2021;Metcalfe & Pickett, 2021).…”
Section: Protest Policing and Attitudes Toward The Policementioning
confidence: 99%